Síntese eletroquímica e caracterização de filmes finos de Sb2Se3 - Costa, Magno Barcelos (Universidade Federal de São Carlos, 2017)
Due to the environmental appeal, the shortage of raw material and the chemical complexity of some systems employed at photovoltaic devices, interest has been growing for semiconductors composed of abundant, low toxicity and less costly elements. Among these, the Sb2Se3 has gained attention, because besides having all the mentioned characteristics, it presents good photovoltaic properties. The present work presents the electro-obtaining of Sb2Se3 thin films, as well as the exploratory study of its properties from the effects of the thermal treatment (TT), the electrodeposition parameters and the addition of Fe2+ as a dopant to its photoelectrocatalytic activity in the reduction reaction of H+. The films were prepared by potentiostatic co-electrodeposition on FTO in a bath composed of K(SbO)C4H4O6 and SeO2 in 0.5 mol L-1 Na2SO4/H2SO4 – pH 2.0. After obtaining, they were submitted to different TT conditions under atmosphere of Se(vapor)/N2. Cyclic voltammetries were used to evaluate the electrochemical process of each separate element and the binary system. For the study of the electrodeposition parameters, the concentrations of the Sb and Se precursors (SbO+ and H2SeO3, respectively), the total deposition charge and the type of the supporting electrolyte were evaluated. Finally, the study of the addition of Fe2+ in the bath allowed to evaluate its effect under different concentrations of the dopant. Thus, through the morphological-structural analysis, band-gap and photoelectrocatalytic activity, it was possible to reach the optimized condition of obtaining Sb2Se3 films. Of all the proposed TT conditions, the one submitted to 300 °C for 3 h showed better results, exhibiting good optoelectronic property and photoactivity, with band gap of 1.08 eV and average photocurrent of 168.15 μA cm-2, respectively. With the study of the electrodeposition parameters allowed to reach the following optimized condition: bath with 2.5 mmol L-1 K(SbO)C4H4O6 and 2.0 mmol L-1 SeO2 in 0.5 mol L-1 Na2SO4/H2SO4 – pH 2.0, and deposition total charge of 600 mC, besides of the applied potential of -0.6 V vs. Ag/AgCl/Cl-(sat. KCl). In the doping study, the incorporation of Fe2+ caused low influence on the band gap of the films and on their morphological-structural properties. In the film obtained from the deposition bath composed of 5% Fe, it presented a similar photocurrent to the non-doped film, however, with carrier density in an order of magnitude three times higher, i.e., 1,0 x 10^19 cm-3, showing an important characteristic for a high efficiency and fill factor in the case a photovoltaic device was installed.
Electrochemical synthesis and characterization of Sb2Se3 thin films
Keywords: Seleneto de antimônio; Fotoeletroquímica; Tratamento térmico; Dopagem; Eletrodeposição; Antimony selenide; Thermal treatment; Doping; Electrodeposition; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::ELETROQUIMICA